2018
DOI: 10.31288/oftalmolzh2019138
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the recurrence after pterygium surgery with the presence of HSV, EBV, CMV, HPV, and BRAFV600E mutation

Abstract: Background: Previously, we have reported on associations of pterygium with the presence of herpes simplex virus (HSV), Epstein Barr virus (EBV), cytomegalovirus (CMV), human papillomavirus (HPV), and the BRAF V600E somatic point. The current study attempted to examine the relationship between the recurrence during 1 year after pterygium surgery and the presence of these factors. Purpose: To identify the relationship between (a) recurrence rates after various surgical techniques for pterygium and (b) the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“… 1 Rykov et al found that carriers of BRAFV600 mutation had an 8-fold increased risk of recurrence during the first year after pterygium surgery. 31 In addition, viruses such as HSV, EBV, CMV, and HPV can be other risk factors for recurrence. 31 …”
Section: R Esultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 Rykov et al found that carriers of BRAFV600 mutation had an 8-fold increased risk of recurrence during the first year after pterygium surgery. 31 In addition, viruses such as HSV, EBV, CMV, and HPV can be other risk factors for recurrence. 31 …”
Section: R Esultsmentioning
confidence: 99%
“…Many authors believe that 97% of recurrences after surgery happen within the first 12 months. 6 31 52 53 54 55 56 …”
Section: R Esultsmentioning
confidence: 99%
“…The correlation of HPV with postoperative recurrence and the absence of HPV in normal conjunctiva and in the subgroup of HPV-infected pterygia with successful resection also raise the query on whether HPV infection represents a cofactor in the pathogenesis of pterygia or whether the altered pterygium surface facilitates autoinoculation of HPV and subsequent postoperative disease relapse. In addition, as other viruses, such as HSV, EBV, and CMV, have been reported as possible risk factors for the development or the postoperative recurrence of pterygium, further analysis of their role in the pathogenesis and in the postoperative disease relapse is necessary [ 5 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…As part of a multistage pathophysiology, viruses can develop pterygium, as one of the dimensions of "second hit" theory in which oncogenic viruses provoke the development of pterygium in genetically susceptible people. 33 The HPV and HSV may have a potential function in the pterygium pathogenesis, based on multiple studies that observed them in pterygium samples. [33][34][35][36][37] The HPV prevalence in pterygium varies from very low to 100%.…”
Section: Diagnosis Of Hpv and Other Viral Etiologies In Pterygiummentioning
confidence: 99%
“…33 The HPV and HSV may have a potential function in the pterygium pathogenesis, based on multiple studies that observed them in pterygium samples. [33][34][35][36][37] The HPV prevalence in pterygium varies from very low to 100%. A meta-analysis reported an overall prevalence rate of 18.6% for HPV infection in pterygium.…”
Section: Diagnosis Of Hpv and Other Viral Etiologies In Pterygiummentioning
confidence: 99%